Nanostructure quantification of turbostratic carbon by HRTEM image analysis: State of the art, biases, sensitivity and best practices. (30th June 2021) - Toth, Pal
Abstract: High Resolution Transmission Electron Microscopy (HRTEM) has been a widely used technique for the analysis of nanostructure of turbostratic carbon. Since the late nineties, digital imaging and image analysis has made it possible to quantify and derive structural properties from HRTEM images. A number of image analysis methodologies have been proposed, based on which numerous studies drew their conclusions about a variety of materials including soot, carbon black, char, black carbon, carbon nano-onions, fullerenes, pyrocarbon, hard carbon, etc. Recognizing the need for standardization in order to make measurements comparable, repeatable and reproducible, this study is a review of published techniques and a critical analysis of a representative set of them. Based on sensitivity analysis using an extensive dataset of micrographs, best practices for image acquisition and image analysis are provided. Measurement uncertainties and sensitivities to image analysis parameters are estimated. A set of improvements to the state-of-the-art is proposed. Computer code for the presented methods is made available. Graphical abstract: Image 1